Preparation and properties of a magnesium phosphate cement with dolomite. (December 2020) - Yu, Jincheng; Qian, Jueshi; Wang, Fan; Li, Zhen; Jia, Xingwen
Abstract: Calcined dolomite containing free-CaO cannot be directly applied in magnesium phosphate cement (MPC) as magnesia raw materials. To chemically combine with CaO and replace magnesite, dolomite-bauxite-gypsum (DBG) powders were calcined to produce MPC containing ye'elimite. The properties of the calcined DBG powders obtained at calcination temperatures no higher than 1300 °C were studied. The performance of these MPC pastes prepared with calcined DBG powders and the hydration process of the new system were also investigated. Results showed that the calcined DBG powders were mainly composed of magnesia, ye'elimite and belite. MPC pastes with calcined DBG powders exhibited high early compressive strength and good volume stability. Ye'elimite was confirmed to participate in the hydration reactions and would also improve the water resistance of the MPC pastes. Some new amorphous hydration products containing Al-P in mesh-like structures were observed during water curing and might be beneficial for the compressive strength development.